Rare bird documentation form for Northern Goshawk at Sweet Marsh, 1984 - Moore, Francis L.et al (1984)
Rare bird documentation form for a Northern Goshawk at Sweet Marsh in Bremer County, IA on January 22, 1984. Epson - sheet feed